2006
DOI: 10.1136/gut.2004.062729
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of high mobility group box 1 (HMGB1) is associated with an elevated level of the antiapoptotic c-IAP2 protein in human colon carcinomas

Abstract: Background: High mobility group box 1 (HMGB1) is a non-histone chromosomal protein implicated in a variety of biologically important processes, including transcription, DNA repair, V(D)J recombination, differentiation, and development. Overexpression of HMGB1 inhibits apoptosis, arguing that the molecule may act as an antiapoptotic oncoprotein. Indeed, increased expression of HMGB1 has been reported for several different tumour types. In this study, we analysed human colon carcinoma for HMGB1 as well as for c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 49 publications
(42 reference statements)
6
124
0
2
Order By: Relevance
“…Although the expression of HMGB1 is under strict developmental control (4,5) and essential for animal survival (6), HMGB1 is apparent in several mature cells (7)(8)(9) as well as in transformed cells (10,11). In cancer cells, HMGB1 supports cell transformation, growth and cellular resistance (11)(12)(13). For this reason, HMGB1 seems to be a crucial factor in cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…Although the expression of HMGB1 is under strict developmental control (4,5) and essential for animal survival (6), HMGB1 is apparent in several mature cells (7)(8)(9) as well as in transformed cells (10,11). In cancer cells, HMGB1 supports cell transformation, growth and cellular resistance (11)(12)(13). For this reason, HMGB1 seems to be a crucial factor in cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…Outside the cell, it bounded firmly to the RAGE receptor which is a potent mediator for inflammation [10]. HMGB1 overexpression inhibits apoptosis, which supports the argument that these molecules may act as antiapoptotic oncoprotein, and HMGB1 expression found increase in several different tumor types [11]. Thus, allegedly HMGB1 translocation from nucleus into the cytoplasm of the cancer cells can affect defense toward apoptosis.…”
Section: Introductionmentioning
confidence: 48%
“…Recent researches have shown that HMGB1 overexpression can improve proliferation [21] and decrease drug sensitivity of cancer cell [22]. In addition, HMGB1 functions as an antiapoptotic oncoprotein by activating NF-κB and the apoptosis inhibitor c-IAP [23]. Moreover, a variety of agents such as cancer chemotherapeutic agents, oncolytic viruses, ultraviolet or gamma irradiation, cytolytic T and nature killer cells that leading to tumor cell death can indicate classic apoptosis markers that were associated with HMGB1 release [24].…”
Section: Discussionmentioning
confidence: 99%